A Silent Voice : See you Later - Book 7 Vol. 7 - Oima, Yoshitoki (New York : Kodansha Comics, 2016)
Shoyas life hangs on by a thread after he jumped just in time to save Shoko. Despite the despair, Shoko is determined to move forward and get back what she thinks she has ruined...But broken friendships can heal, too... (From back cover).
Rated T for ages 13+.
Keywords: Deaf children -- Comic books, strips, etc; Conduct of life -- Comic books, strips, etc; Bullies -- Comic books, strips, etc; Bullying -- Comic books, strips, etc; School children -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Teenagers -- Comic books, strips, etc; Graphic novels -- Japan; Translations into English; Comic books, strips, etc. -- Japan; Translations into English; Manga; Graphic novels; Manga (Comic books, strips, etc.).